Pseudoaneurysm following Surgical Resection of Craniopharyngioma: What Is the Best Management? - del Pont, Francisco Marco; Villalonga, Juan Francisco; Sáenz, Amparo; Caffaratti, Guido; Alcorta, Santiago Condomi; Cervio, Andrés (Indian Journal of Neurosurgery, 2021)
Craniopharyngiomas are benign tumors of the sellar and parasellar region for which surgical resection remains the treatment of choice. There are many publications on the most frequent postoperative complications, but few reports on subclinical lesions affecting the arteries of the circle of Willis, despite their high morbidity and mortality rate. Trauma-induced aneurysms are infrequent, representing less than 1% of intracranial aneurysms. Iatrogenic intracranial pseudoaneurysms are a subtype of surgically induced aneurysms developed as a result of direct injury to the arterial wall or after dissection of tumors adherent to the vessel adventitia. The natural history of these lesions is not well known because their incidence is extremely low. We report two cases of postoperative aneurysms of the internal carotid artery after craniopharyngioma resection and a brief review on the management of such lesions.
Keywords: carotid artery injuries; craniopharyngioma; pseudoaneurysm; postoperative complication; aneurysm